Association between Body Mass Index and Left Ventricular Ejection Fraction in Obese Patients with Atrial Fibrillation Referred for Catheter Ablation - Wan, Rong; Su, Yuhao; Huang, Ying (Frontiers in Nutrition, 2026)
BackgroundAtrial fibrillation (AF) is one of the most common arrhythmias associated with obesity and metabolic disorders. However, little is known about the association between body mass index (BMI) and left atrial size and left ventricular ejection fraction (LVEF) in AF patients referred for catheter ablation.MethodsWe retrospectively obtained a dataset (N = 170) from the Dryad database, in which the association between alcohol consumption, cardiac biomarkers, left atrial size, and re-ablation in patients with AF referred for catheter ablation was analyzed as part of the SMURF (Symptom burden, Metabolic profile, Ultrasound findings, Rhythm, neurohormonal activation, haemodynamics and health-related quality of life in patients with atrial Fibrillation) study. Multivariable linear regression models were used to investigate the association between baseline BMI and left atrial size and LVEF in these patients.ResultsCorrelation analysis displayed that BMI was negatively associated with LVEF, but it had no correlation with left atrial volume (LAV)/body surface area (BSA). When evaluating BMI as an independent variable, our linear regression analysis for adjusted coefficient of LVEF [correlation coefficient = −0.46, 95% CI: (−0.78, −0.15), p = 0.0049] was very significant after age, gender, smoking, alcohol consumption and estimated glomerular filtration rate (eGFR) were controlled for. However, the correlation coefficients for LAVmax/BSA and LAVmin/BSA were −0.01 and 0.13, respectively, and were not statistically significant after adjusting for the same covariates.ConclusionWe observed that BMI had a significantly negative correlation with LVEF but not with LAVmax/BSA or LAVmin/BSA in the obese patients with AF referred for catheter ablation. This suggests that obesity may be associated with an increased risk of impaired cardiac contractile function in these patients.